Image Processing Algorithm for the Assessment of the Ore Fragmentation Size Distribution - Firla, Marcin; Lipnicki, Piotr; Lewandowski, Daniel (Proceedings (IEEE International Conference on Emerging Technologies and Factory Automation), 2019)
The article presents the description of an image processing algorithm that attempts to estimate the fragmentation size distribution of ore. An introduction to the subject is followed by a step-by-step description of the algorithm. The result of the algorithm is in a form of a histogram containing information on the size of the objects detected with the use of the routine. Even though the algorithm has shown to provide promising results, some important observations have been made which point towards areas where the algorithm could be improved. The designed solution was evaluated by means of experiments conducted in two different test stands - rotary table conveyor belt and standard conveyor belt. The samples for fragmentation size distribution has been prepared beforehand according to appropriate guidelines.